May the Phage be With You? Prophage-Like Elements in the Genomes of Soft Rot Pectobacteriaceae: Pectobacterium spp. and Dickeya spp. - Czajkowski, Robert (Frontiers in Microbiology, 2019)
Soft Rot Pectobacteriaceae (SRP; Pectobacterium spp. and Dickeya spp., formerly known as pectinolytic Erwinia spp.) are necrotrophic bacterial pathogens infecting a large number of plant species worldwide, including agriculturally-important crops. Despite the SRP importance in agriculture, little is known about the bacteriophages infecting them, and even less about the prophages present in their genomes. Prophages are recognized as factors underlying bacterial virulence, genomic diversification and ecological fitness that contribute to the novel phenotypic properties of bacterial hosts. Likewise, they are recognized as a driving force of bacterial evolution. In this study, 57 complete genomes of Pectobacterium spp. and Dickeya spp. deposited in NCBI GenBank, were analyzed for the presence of prophage-like elements. Viral sequences were discovered in 95% of bacterial genomes analyzed with the use of PHASTER, PhiSpy, and manual curation of the candidate sequences using NCBI BLAST. In total 37 seemingly intact and 48 putatively defective prophages were found. The 37 seemingly intact prophages (27 sequences in Dickeya spp. genomes and 10 sequences in Pectobacterium spp. genomes) were annotated using RAST. Analysis of the prophage genes encoding viral structural proteins allowed classification of these prophages into different families of the order Caudovirales (tailed bacteriophages) with the SRP prophages of the Myoviridae family (81% of found prophages) being the most abundant. The phylogenetic relationships between prophages were analyzed using amino acid sequences of terminase large subunit (gene terL), integrase (gene int), holin (gene hol), and lysin (gene lys). None of these markers however proved fully useful for clear phylogenetic separation of prophages of SRP into distinct clades. Comparative analyses of prophage proteomes revealed six clusters: five present in Dickeya spp. and one within Pectobacterium spp. When screened for the presence of bacterial genes in the genomes of intact prophages, only one prophage did not contain any ORFs of bacterial origin, the other prophages contained up to 23 genes acquired from bacterial hosts. The bacterial genes present in prophages could possibly affect fitness and virulence of their hosts. The implication of prophage presence in the genomes of Pectobacterium spp. and Dickeya spp. is discussed.